(untitled) (Journal of Nepal Geological Society, 2000)
This study deals with five landslide dams in the Nepal Himalayas. Two of them (i.e. Tai and Latamrang) are situated within the Higher Himalayan Crystallines of the Annapurna region, one (i.e. Ringmo) lies within the Tibetan-Tethys Zone of Dolpa, and remaining two (i.e. Ghatta Khola and Darbang) are located within the Lesser Himalayan rocks. All of them formed a more-or-less stable lake upstream by damming the main river. In this paper, an attempt has been made to work out the stability conditions of these dams and their risk of failure. Generally, the stability of such dams is attributed to their morphology, volume of debris as well as its composition and size of clasts. Based on the study of these five cases and another well-known example from the Himalayas (i.e. Ghona Tai), it can be shown that there are other following important factors affecting the stability of landslide dams: - type of movement (sliding, avalanching, in situ collapse); - grain size distribution of the landslide debris (boulders, not disintegrated and interlocked blocks, shattered and crushed material); - possibility of mixing of the landslide debris with the glacial deposits; - possibility of secondary cementation of the landslide debris (by seepage water, transported sediments , mineralised thermal waters); - climatic conditions; and - rate of sedimentation in the lake.